Oxford handbook of criminal process - Brown, Darryl K.; Turner, Jenia I.; Weisser, Bettina (Oxford University Press London, 2019)
Examining various aspects of the criminal process, this handbook covers topics ranging from criminal process in the dual penal state to interrogation law, and trial procedure in response to terrorism. There eight sections, with chapters on the role of prosecutors in common law and civil law jurisdictions, the rights and duties of experts, victim rights in civil law jurisdictions, surveillance and investigation, criminal prosecution and its alternatives, evidence discovery and disclosure in common law systems, evidence law as forensic science, common law plea bargaining, appeals and post-conviction review, and procedure in international tribunals.
Criminal Process in the Dual Penal State: A Comparative-Historical Analysis / Markus D. Dubber -- Defense Rights, Duties, Norms and Practices in Common Law and Civil Law Jurisdictions / Ed Cape -- Professional Judges, Lay Judges, and Lay Jurors / Valerie Hans, Rebecca Helm -- Rights and Duties of Experts / Joelle Vuille -- Conceptualizing the Victim within Criminal Justice Processes in Common Law Tradition / Marie Manikis -- Victim Rights in Civil Law Jurisdictions / t Detention before Trial and Civil Detention of Dangerous Individuals in Civil Law Jurisdictions / Grischa Merkel -- Pretrial Detention and Civil Detention of "Dangerous" Individuals in Common Law Jurisdictions / Bernadette McSherry -- Empirical Approaches to Criminal Procedure / Jacqueline Hodgson, Yu Mou -- Access to and Limits on Evidence Dossiers in Civil Law Systems / Michele Caianiello -- Transnational Access to Evidence, Witnesses and Suspects / Sabine Gless -- International Law and Treaty Obligations, Mutual Legal Assistance and E.U. Instruments / t Common Law Plea Bargaining / Mary Vogel -- Forensic Science Evidence, Adversarial Criminal Proceedings and Mainstream Scientific "Advice" / Gary Edmond -- Comparative Approaches to Criminal Procedure: Transplants, Translations and Adversarial-Model Reforms in European Criminal Process / Eliabetta Grande -- Beyond Common Law Evidence: Reimagining, and Reinvigorating, Evidence Law as Forensic Science / John Jackson, Paul Roberts -- Exclusion of Wrongfully Obtained Evidence: A Comparative Analysis / Ho Hock Lai -- Rights and Methods to Challenge Evidence and Witnesses in Civil Law Jurisdictions / Lorena Bachmaier -- The Confrontation Right / Richard Friedman -- Comparative Assessment of Sentencing Laws, Practices and Trends / t Criminalization and Quasi-Criminalization of Terrorism: Emerging Trends and Tensions with Human Rights Law in the UK / Helen Fenwick -- The European Union and the Rights of Individuals in Criminal Proceedings / Valsamis Mitsilegas -- Roles, Powers, Procedure and Practice: The Place of the Prosecutor in Common Law and Civil Law Jurisdictions / Katalin Ligeti.
Includes bibliographical references and index.
Specialized.
Keywords: Criminal procedure; Criminal law; Criminal justice, Administration of; Criminal procedure -- European Union countries